Effects of a moderate-to-high intensity resistance circuit training on fat mass, functional capacity, muscular strength, and quality of life in elderly: A randomized controlled trial - Pablo Jorge Marcos-Pardo (Nature Portfolio, 2019)
Abstract Physical exercise is considered an important intervention for promoting well-being and healthy aging. The objective was to determine the effects of moderate-to-high intensity resistance circuit training on different parameters of body composition, functional autonomy, muscular strength and quality of life in elderly. A randomized controlled trial was conducted. A total of 45 subjects (27 females, 18 males) aged between 65–75 years old from Murcia (Spain) were divided by sex, and randomly to experimental group (n = 33, mean age 69 ± 3.2 years old) receiving 12 weeks of moderate-to-high intensity resistance circuit training and control group (n = 33, mean age 70 ± 4.1 years old) receiving no exercise intervention. Intra-group comparison, the experimental group showed a significant increment of lean body mass in women and men, which also presented a decrease of fat mass. Both sex presented a significant improve in functional autonomy, and significately higher values of muscular strength. But no changes were observed regarding quality of life in these groups. The control group did not show any differences pre and post-intervention in women, but in men presented an increment of body mass index and total weight post-intervention. No changes were showed in the other variables. Similar results were founded at inter-group comparison. The moderate-to-high intensity resistance circuit training showed increase in total lean body mass, improvements in functional capacity and significantly increase in upper and lower muscular strength in women and men. Progressive resistance circuit training should be promoted for the elderly as it has the potential to improve physical performance, thereby prolonging healthy independent aging.